2022
DOI: 10.1038/s41598-022-27162-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased moist heat stress risk across China under warming climate

Abstract: Heatwaves have afflicted human health, ecosystem, and socioeconomy and are expected to intensify under warming climate. However, few efforts have been directed to moist heat stress (MHS) considering relative humidity and wind speed, and moist heat stress risk (MHSR) considering exposure and vulnerability. Here we showed MHS and MHSR variations across China during 1998–2100 using China Meteorological Administration Land Data Assimilation System datasets, the 6th Coupled Model Intercomparison Project (CMIP6) mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Hu et al studied the performance of five different resolution reanalysis temperature products in the permafrost region of the Qinghai Tibet Plateau, including CFSR, ERA-Interim, GLDASNOAH, MERRA, JRA-55, and CMFD, of which ERA-Interim has a better overall performance [54]. Sun et al compared the daily maximum temperature performance of CLDAS, ERA5, and GLDAS in the Chinese Mainland, and found that the high-resolution CLDAS is significantly better than the other two products [55]. From the above research, it can be seen that the performance of high-resolution temperature data in intergenerational reanalysis data is usually better than that of low-resolution data in the same year, and high-resolution reanalysis temperature data can better depict small and medium-sized fine features.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al studied the performance of five different resolution reanalysis temperature products in the permafrost region of the Qinghai Tibet Plateau, including CFSR, ERA-Interim, GLDASNOAH, MERRA, JRA-55, and CMFD, of which ERA-Interim has a better overall performance [54]. Sun et al compared the daily maximum temperature performance of CLDAS, ERA5, and GLDAS in the Chinese Mainland, and found that the high-resolution CLDAS is significantly better than the other two products [55]. From the above research, it can be seen that the performance of high-resolution temperature data in intergenerational reanalysis data is usually better than that of low-resolution data in the same year, and high-resolution reanalysis temperature data can better depict small and medium-sized fine features.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that these hiatuses are caused by natural external forcing, while others believe that they are triggered by the internal variability of the climate system [18]. The occurrence of hiatuses is partially attributed to La Niña-like cooling in the eastern tropical Pacific Ocean [19]. The weakening of the polar stratospheric vortex leads to hiatuses in Eurasia in winter [20,21].…”
Section: Introductionmentioning
confidence: 99%